Navigating the Digital Micro Environment: A Bibliometric Analysis of Strategy Development Trends - Athhar Sutanto, Hariz; Firmansah, Faizal; Setiawan, Adi (Malikussaleh University, Aceh, Indonesia, 2025)
The development of digital technology has led to significant changes in the business environment, especially in the context of digital micro. The digital micro-environment includes essential elements such as digital customers, digital competitors, business partners, suppliers, and connected digital platforms in a dynamic ecosystem. This article applies qualitative research methods with a historical approach to identify developments, trends, or research mapping related to strategy development in the digital microenvironment. This analysis supports understanding strategic research developments, trends, or mapping in the current micro-digital environment. It provides recommendations for future research themes or variables for researchers. In the Co-authorship analysis, some authors are connected to other authors. The results of this analysis show that the authors collaborated in research on developing strategies in the digital microenvironment; Li collaborated with other authors on three published articles, which were worked on by two research teams. The development of strategy in the digital microenvironment continues to increase, especially from 2016 to 2021. Based on Vos Viewer analysis, 141 variables were obtained in the strategy theme in the digital microenvironment. The competitive advantage variable with a weight or Total link strength is 78. The variable with the most weight or Total link strength of the two social media influencers is 59. Based on Vos Viewer analysis, 141 variables were obtained in the strategy theme in the digital microenvironment.